2017
DOI: 10.1371/journal.pone.0171229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of C-reactive protein to predict treatment response during cystic fibrosis pulmonary exacerbations

Abstract: RationaleC-reactive protein (CRP) is a systemic marker of inflammation that correlates with disease status in cystic fibrosis (CF). The clinical utility of CRP measurement to guide pulmonary exacerbation (PEx) treatment decisions remains uncertain.ObjectivesTo determine whether monitoring CRP during PEx treatment can be used to predict treatment response. We hypothesized that early changes in CRP can be used to predict treatment response.MethodsWe reviewed all PEx events requiring hospitalization for intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
18
1
Order By: Relevance
“…Tools to predict response to exacerbation therapy could optimize care and allow more precise anticipatory guidance to patients. Change in C‐reactive protein (CRP) from days 0 to 5 of IV antibiotic therapy did not predict response in an analysis of 83 exacerbations from 2013 to 2015 in a single hospital . However, very high CRP (>75 mg/L) at admission predicted non‐response and CRP level at admission predicted time to next exacerbation, demonstrating the potential utility of CRP as a clinical predictor for exacerbations.…”
Section: Epidemiologymentioning
confidence: 99%
“…Tools to predict response to exacerbation therapy could optimize care and allow more precise anticipatory guidance to patients. Change in C‐reactive protein (CRP) from days 0 to 5 of IV antibiotic therapy did not predict response in an analysis of 83 exacerbations from 2013 to 2015 in a single hospital . However, very high CRP (>75 mg/L) at admission predicted non‐response and CRP level at admission predicted time to next exacerbation, demonstrating the potential utility of CRP as a clinical predictor for exacerbations.…”
Section: Epidemiologymentioning
confidence: 99%
“…7 A study of 27 patients reported that the CRP level was not associated with the severity of pulmonary exacerbations but was associated with specific clinical characteristics, which included Pseudomonas and Aspergillus infection and treatment with corticosteroids. 9 Loh et al assessed the role on CRP and procalcitonin and erythrocyte sedimentation rate in acute exacerbations of CF. 9 Loh et al assessed the role on CRP and procalcitonin and erythrocyte sedimentation rate in acute exacerbations of CF.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…8 Sharma et al found that the admission CRP predicted treatment non-response and time until next exacerbation. 9 Loh et al assessed the role on CRP and procalcitonin and erythrocyte sedimentation rate in acute exacerbations of CF. They found CRP levels rise with exacerbations.…”
Section: Brief Communicationsmentioning
confidence: 99%
“…In ammation is a pathophysiologic hallmark of CF (21), but limited information exists about correlations between in ammatory mediator levels and lung function (22)(23)(24) or HRQoL (22) during PEXs because few studies have monitored PwCF throughout a complete PEX cycle (i.e., from baseline health to PEX onset and serially during PEX treatment to recovery). Accordingly, there remains a need to identify biochemical tests that are easily performed in clinical laboratories and are able to identify groups of PwCF with different physiologic and symptomatic responses to PEX treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there remains a need to identify biochemical tests that are easily performed in clinical laboratories and are able to identify groups of PwCF with different physiologic and symptomatic responses to PEX treatment. Concentrations of certain cytokines and protein effectors of in ammation in blood and sputum from PwCF measured before, during, and after PEXs could have diagnostic and prognostic utility (12,(24)(25)(26)(27). With the exceptions of calprotectin and C-reactive protein, clinical laboratories do not routinely quantify these substances in biological samples, which is a barrier to their widespread application as tools to monitor PEX treatment responses (28,29).…”
Section: Introductionmentioning
confidence: 99%